Analisis Konsep Lean Thinking Pelayanan Laboratorium pada Pasien UGD Rs Masmitra Bekasi - Sari, Relia (UI Scholars Hub, 2015)
Thesis describes the improvement of quality and laboratory services at. Masmitra Hospital through Lean method which aims to create value by reducing errors and waiting time. This study is a qualitative analytical research method by observation, interviews and data analysis to analyze the flow process of laboratory services for ER patients. The results showed that laboratory services at Masmitra Hospital still found delays which is prooven on the Current State Value Stream Map where 39% of the activities are non-value - added and 7 types of waste as well as through the aplication of Lean Tools has created improvement ideas in Future State Value Stream Map where there are only 9 % of non value-added activities in the process. Therefore, the application of the concept of lean thinking is appropriate to improve the quality of laboratory services at Masmitra Hospital